2012
DOI: 10.1002/asna.201211675
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability analysis of the Hall magnetorotational instability in a spherical domain

Abstract: We investigate the stability of the Hall-MHD system and determine its importance for neutron stars at their birth, when they still consist of differentially rotating plasma permeated by extremely strong magnetic fields. We solve the linearised Hall-MHD equations in a spherical shell threaded by a homogeneous magnetic field. With the fluid/flow coupling and the Hall effect included, the magnetorotational instability and the Hall effect are both acting together. Results differ for magnetic fields aligned with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…With spherical models it has been shown that the growth rates of SHI scale with the rotation rate and not with the rather long Hall time [191,192]. The dispersion relation (126) leads to the same conclusion.…”
Section: The Shear-hall Instability (Shi)mentioning
confidence: 79%
See 1 more Smart Citation
“…With spherical models it has been shown that the growth rates of SHI scale with the rotation rate and not with the rather long Hall time [191,192]. The dispersion relation (126) leads to the same conclusion.…”
Section: The Shear-hall Instability (Shi)mentioning
confidence: 79%
“…It is then easy to calculate the magnetic Mach number as Mm = Rm/S. In all cases with Pm < ∼ 1 the instability exists for rapid rotation with Mm > 1.With spherical models it has been shown that the growth rates of SHI scale with the rotation rate and not with the rather long Hall time[191,192]. The dispersion relation(126) leads to the same conclusion.…”
mentioning
confidence: 82%
“…They showed that the MRI of a Kepler flow is significantly modified by the Hall effect depending on the orientation of the magnetic field in relation to the rotation axis. Kondić et al (2012Kondić et al ( , 2011 investigated the stability of the Hall-MHD system for a spherical shell and determined its importance for newborn neutron stars. Similarly, their re-sults differ for magnetic fields aligned with the rotation axis and anti-parallel magnetic fields.…”
Section: Introductionmentioning
confidence: 99%